2004
DOI: 10.1590/s1678-77572004000300010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of two types of ceramic inlays and onlays after 6 months

Abstract: he aim of the present study was to evaluate the clinical performance of two types of ceramics: a slurry-powder ceramic (Duceram Plus, Degussa) -D and a hot-pressed leucite-based glass-ceramic (IPS Empress, Ivoclar Vivadent) -IPS. Eighty-six restorations, 44 IPS and 42 D, were made by one operator. A total of 33 onlays and 53 inlays on twenty-seven premolars and 59 molars were cemented in 35 patients of both sexes, mean age 35 years. All restorations were cemented with the dual-resin cement (Variolink, Ivoclar-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Fradeani et al reported that marginal discoloration and marginal integrity were interrelated, and both would deteriorate with time . This fact can be attributed to the wear of resin luting cement, which was considered to be one critical aspect of adhesively luted ceramic restorations . This was found in some prospective studies, in which the marginal adaptation was the criterion with the lowest Alpha ratings and may also have affected the results of this study, provided the timeframe for follow‐up was longer.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Fradeani et al reported that marginal discoloration and marginal integrity were interrelated, and both would deteriorate with time . This fact can be attributed to the wear of resin luting cement, which was considered to be one critical aspect of adhesively luted ceramic restorations . This was found in some prospective studies, in which the marginal adaptation was the criterion with the lowest Alpha ratings and may also have affected the results of this study, provided the timeframe for follow‐up was longer.…”
Section: Discussionmentioning
confidence: 67%
“…In the present study, GIC was used as a base to block out undercuts, helping to standardize the depth of the pulpal floor and reducing the loss of tooth substance during cavity preparation. 31 GIC bases may reduce the risk of cusp fracture during the time between cavity preparation and the insertion of adhesive inlays. 23 It seems that depth of the preparation and the remaining inter-axial thickness were among the most critical factors that reduced the fracture resistance of teeth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several developments have taken place in these areas resulting in the production of ceramic materials for clinical use. These include the aluminous porcelain crown (Vitadur, Vita Zahnfabrik, Bad Säckingen, Baden-Württemberg, Germany), the non shrink ceramic crown (Cerestore, Johnson and Johnson, East Windsor, NJ, USA), the castable mica glass-ceramic crown (Dicor, Caulk/Dentsply, Milford, DE, USA) and the leucite-reinforced glass ceramics (IPS Empress, Ivoclar Vivadent, Schaan, Liechtenstein) 8,20,22,26,32 . All these all-ceramic systems exhibit low flexural strengths (100-150 MPa), which make them at risk of failure when used for the construction of either posterior crowns or fixed partial dentures 12,21,23 .…”
Section: Introductionmentioning
confidence: 99%